Inhibition of DHFR targets the self-renewing potential of brain tumor initiating cells. (10th April 2021) - Fawal, Mohamad-Ali; Jungas, Thomas; Davy, Alice
Abstract: Brain tumors are a heterogeneous group of benign and malignant tumors arising from the brain parenchyma and its surrounding structures, with in general a poor clinical outcome due to high recurrence. One of the underlying causes for this somber prognostic is the presence of brain tumor initiating cells (BTIC) endowed with self-renewal potential, multi-lineage differentiation and resistance to treatment. One promising therapeutic avenue for brain tumors is targeting BTIC self-renewal potential and forcing their differentiation. A compelling candidate is one-carbon metabolism shown to play a key role in maintaining stem cell self-renewal in several lineages. Here, we focus on dihydrofolate reductase (DHFR), a key enzyme in one-carbon metabolism, and demonstrate this enzyme's overexpression in several human brain tumors and its expression in human BTIC. We show that DHFR inhibition, either by Methotrexate (MTX) or EphB activation with synthetic ligands, reduces the tumorigenic potential of 4 human BTIC lines, by reducing their self-renewal capacities both in vitro and in a cerebral organoid glioma (GLICO) model. Our data indicate that driving BTIC differentiation by inhibiting DHFR may provide a new therapeutic approach to treating highly refractory aggressive tumors. Highlights: Description of DHFR expression and Eph:Ephrin signalling in human brain tumor samples. Eph activation reduces DHFR expression and activity in BTIC. Eph activation counteracts the increased DHFR protein level following MTX treatment. Inhibition of DHFR activity impinges on BTIC self-renewal in vitro. Inhibition of DHFR activity limits the expansion of BTIC grafted in human cerebral organoids.